The Effect of Tool Press Force to Weldability of AA5754 and AA6061 Alloys with Friction Stir Welding Method - Hasan Yılmaz; Semih Mahmut Aktarer; Tevfik Küçükömeroğlu (Pamukkale University Journal of Engineering Sciences, 2013)
In this study AA5754 and A6061 alloys have been butt welded to each other by using friction stir welding (FSW). At constant tool geometry and tool angle experiments were carried out, joints were performed using different welding speed, rotation speed and especially tool press force. The mechanical properties of the welded samples were determined by using tensile test, bending test and micro hardness. Generated microstructure and hardness profile was obtained in the welding zone. In this friction stir welding study the parameters which affect the joint structure are the tool press force, welding speed and tool rotation speed which were determined. At the end of study it is determined that AA5754 and AA6061 alloys can be successfully welded by using Friction Stir Welding method under different tool press forces at least 6kN.